The application of Sharia law in the resolution of Islamic economic disputes in Indonesia - Moh. Idrus (Journal of Innovative and Creativity, 2025)
This study examines the application of Sharia law in the resolution of Islamic economic disputes in Indonesia. As a country with the largest Muslim population, Indonesia has developed a unique legal framework that integrates Islamic principles into its national legal system, particularly concerning financial transactions and disputes. This abstract explores how Sharia law, derived from the Qur'an and Sunnah, is applied in various dispute resolution mechanisms for Islamic economic activities, including mediation, arbitration, and litigation within the religious courts. It analyzes the challenges and opportunities presented by this integration, such as issues of legal certainty, enforceability of Sharia-compliant contracts, and the competency of judicial bodies. The study highlights the increasing role of Sharia economic courts and national arbitration bodies in providing specialized and effective solutions for these disputes. Ultimately, this research contributes to understanding the evolving landscape of Islamic finance and dispute resolution in Indonesia, offering insights into the harmonization of religious and secular legal systems to foster a stable and just economic environment.